Wyznaczanie racjonalnej wielkości przedsiębiorstwa handlowego w środowisku wielkomiejskim (na przykładzie branży owocowo-warzywnej) - Michalak, Adolf; Świtajski, Rajmund (Wydział Prawa i Administracji UAM, 1986)
Against the background of the presentation of theoretical directions of the search for the rational size of a trade enterprise, the article presents the algorythm of proceedings facilitating the evaluation of that size, it is exemplified by means of the empirical data concerning the fruit and vegetable branch in Poznań. Although the procedure of approaching the problem solution presented in the article is not the sole one, it can become a contribution to the research on possibilities of evaluating the optimum size of a trade enterprise.
Evaluating the Rational Size of a Trade Enterprise in Urban Environment (on the Example of Fruit — Vegetable Selling Branch)